Spontaneous excision of a large composite transposable element of Drosophila melanogaster. - Chia, W.; McGill, S.; Karp, R.; Gubb, D.; Ashburner, M. (Nature, 1985)
The TE1 family of transposable elements (TEs) of Drosophila consists of unusually large transposons, cytologically visible in larval polytene chromosomes as one or more bands. They are composite elements, as their termini consist of foldback (FB) sequences which are themselves transposable. The location of FB elements at the termini of transposable elements suggests that these sequences have a direct role in the genetic instability of TEs. To investigate the structural and phenotypic consequence of TE excision, we have cloned genomic DNA required for the expression of the no-ocelli (noc) gene of Drosophila; this gene has been mutated by the insertion of TE146, a member of the TE1 family carrying six polytene chromosome bands including functional copies of the white (w+) and roughest (rst+) genes. As reported here, our experiments indicate that the spontaneous excision of TE146, which results in the loss of the w+ and rst+ markers, can occur either as a single-step event or following a partial internal deletion. In either case, the end product is an imprecise excision in which a residual portion of the element, varying in size from 3 to 10 kilobases (kb), is left at the insertion site. These residual sequences share homology with the FB family. Furthermore, despite their imprecise nature, all these spontaneous excisions restore a wild-type noc+ phenotype.